Data literacy and higher education in the 21st century - Oluwatosin Abiodun Ologbosere (IASSIST Quarterly, 2023)
Data Literacy is a germane competence for anyone or institution desirous to scale the challenges of the 21st century and be globally recognized. Data literacy is the ability of individual to identify, work with, analyze and communicate data effectively. It is perceived that there is a poor data literacy competence in higher institutions in developing countries. Researchers in the 21st century, for example, ought to possess skills and competencies to communicate through affiliated institutional email addresses;  be active on platforms such as Google scholar and research gate; and, possibly own personal websites to drive teaching and learning. This paper, through qualitative analysis of existing literature, attempts to examine the interplay between data literacy and higher education in the 21st century. Data Literacy is relevant not only to individuals but also to higher education.  The phenomenon data literacy is relevant to institutions of higher learning because institutions of higher learning are acknowledged centers of human resources training for national and sustainable development. The paper will be of significance to governments, policy makers, and administrators of higher institution in particular. Furthermore, the paper will be of benefit to scholars as data literacy continues to shape frontiers of teaching and learning across the globe in the 21st century.